1992 American Control Conference 1992
DOI: 10.23919/acc.1992.4792174
|View full text |Cite
|
Sign up to set email alerts
|

Review and Unification of Reduced Order Force Control Methods

Abstract: In this article, we compare some of the recent methods developed for simultaneous position and force control of a single n-link constrained robot manipulator. Mathematical models of the constrained manipulator are introduced and the advantages and disadvantages of the associated control formulations are discussed. The similarities between each of the proposed formulations are also highlighted. Finally, a transformation is presented that generalizes the methods of decoupling force from the position dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
1995
1995

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…Given that the main purpose of this paper is to present experimental results, we will use this section to briefly highlight the important points found in the theoretical developments described by Grabbe et al, 2 and to make clear the various terms found in the final control law.…”
Section: Dynamic Models and Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the main purpose of this paper is to present experimental results, we will use this section to briefly highlight the important points found in the theoretical developments described by Grabbe et al, 2 and to make clear the various terms found in the final control law.…”
Section: Dynamic Models and Constraintsmentioning
confidence: 99%
“…An adaptive motion control scheme was developed 89 which was based on the constrained joint-space robot model formulation given in reference 1. Grabbe et al 2 developed a robust controller based on work in reference 1 to compensate for parametric uncertainty and additive bounded disturbances. Other work concerning constrained robot manipulation is given in references 10-14.…”
Section: Introductionmentioning
confidence: 99%
“…This important research area has recently attracted the attention of many researchers, and interesting results related to state variable representation, feedback linearization, and control and stabilization of constrained dynamic systems have been reported. [13][14][15][16][17][18][19][20][21][22][23] Sliding mode controllers for contrained motion and force control have been de-~i g n e d .~~,~ However, in these papers, position and force control of robotic arms with only rigid links have been considered. Some research related to position and force control of robots with elastic joints has been also done.…”
Section: Introductionmentioning
confidence: 99%
“…This intensive study has produced many approaches to achieving compliant motion, including hybrid position/force control, 1 " 3 impedance control,*"* admittance control, 7 and reduced-order force control. 8 " 10 It is interesting to briefly characterize these strategies, in terms of the control objective associated with the "compliant part" of the task. From this perspective, two broad classes of compliant motion control schemes can be identified: force controllers and impedance controllers.…”
Section: Introductionmentioning
confidence: 99%